RELAPSE OF GRAVES’ DISEASE FOLLOWING A PREGNANCY: A SINGLE CENTRE PROSPECTIVE OBSERVATIONAL STUDY - Chai, Shu Teng; Lee, Siow Ping; Loh, Leh Teng (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Relapse of Graves’ disease (GD) is common in the postpartum period. One study showed that the overall relapse rate of GD following a pregnancy was 84%, as compared to that of 56% in women who did not become pregnant. We aim to determine the prevalence of relapsed GD during postpartum period in our centre. METHODOLOGY All pregnant women who were diagnosed with Graves’ disease either before or during index pregnancy in endocrine clinic from October 2016 to May 2018 were followed up monthly throughout their gestation and 3- monthly after delivery till one year postpartum. All were managed according to standard care. Relevant demographic and clinical data were collected during outpatient visits. RESULTS Thirty-six patients (50% Malay, 33.3% Chinese, 2.8% Indian and 13.9% others) fulfilled the inclusion criteria. Median [interquartile range (IQR)] age and period of gestation at recruitment were 29 years old (25, 32.75) and 17.5 weeks (12, 23.5) respectively. Nearly half (47.2%) were diagnosed with GD within one to five years prior while only 8 (22.2%) had the diagnosis made during index pregnancy. Median (IQR) free thyroxine (T4) during the first trimester was 34.77 pmol/L (18.39, 77.46). Out of 16 patients in whom one-year postpartum data were available, half received antithyroid treatment throughout pregnancy and postpartum period while the other half had antithyroid medications withheld during gestation. Six (75% of eight patients) experienced relapse of GD after delivery. Median (IQR) time between delivery and relapse was 4.5 months (1.75, 6.50). Maternal age, duration of GD, timing of GD diagnosis in relation to index pregnancy and antenatal antithyroid treatment did not influence postpartum relapse of GD. CONCLUSION Three quarter of our pregnant women who had GD experienced relapse at approximately 4.5 months after delivery. Close monitoring of postpartum thyroid function is pertinent to avoid adverse complications.